2019
DOI: 10.1590/s0100-83582019370100134
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Phytoremediation Potential of Castor Cultivars for Heavy Metals from Soil

Abstract: Phytoremediation is a useful tool to restore heavy metals contaminated soils. This study was carried out to test two castor (Ricinus communis) cultivars [Local and DS-30] for phytoextraction of heavy metals from the soil spiked by known concentrations of seven metals (Cu, Cr, Fe, Mn, Ni, Pb and Zn). A pot experiment was laid out by using a completely randomized design. Soil and plant samples were analyzed at 100 days after planting. The data on heavy metal uptake by plant tissues (roots, leaves and shoots) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In contrast, LEV's safety profile is remarkably positive, with negligible serious adverse effects reported across multiple studies, even at high doses for seizure control [6,16]. This reinforces the potential of LEV as a safer alternative to PB in neonatal seizure management, a sentiment echoed by our findings and supported by recent randomised controlled trials (RCTs) [5,14].…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, LEV's safety profile is remarkably positive, with negligible serious adverse effects reported across multiple studies, even at high doses for seizure control [6,16]. This reinforces the potential of LEV as a safer alternative to PB in neonatal seizure management, a sentiment echoed by our findings and supported by recent randomised controlled trials (RCTs) [5,14].…”
Section: Discussionsupporting
confidence: 81%
“…Angelova et al (2020) suggested that the castor oil plant is tolerant to heavy metals and bioaccumulation factor and translocation factor values were recorded greater than one, which shows the heavy metal accumulation efficiency in the shoots of castor plant. Screening of metal-tolerant R. Communis cultivars is very effective method to utilize for the remediation of metalcontaminated soils, owing to their high capacity for metal tolerance (Akwasi Yeboah et al 2020;Khan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%